High-strength corrosion-resistant aluminum alloy material as well as preparation method and application thereof
By regulating the content and mass ratio of Mg, Zn, and Cu elements in aluminum alloy materials, and combining the addition of trace elements and aging strengthening, a high-strength corrosion-resistant aluminum alloy material suitable for the marine atmospheric environment is formed, which solves the problem that the strength and corrosion resistance of active aluminum alloy materials in marine atmospheric environments is difficult to take into account, and the high strength and excellent corrosion resistance of the material are achieved.
Patent Information
- Application Number
- CN202510067683.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
It is difficult for active aluminum alloy materials to take into account strength and corrosion resistance when serving in the marine atmospheric environment, and cannot meet the strict needs of ships, carrier-based aircraft, radar and other equipment.
By accurately controlling the content and mass ratio of Mg, Zn, and Cu elements in aluminum alloy materials, and through aging strengthening, we ensure the dispersion and precipitation of T-Mg32(Al, Zn)49 phase and its metastable phase, combined with the addition of trace elements, we form microstructure characteristics that are conducive to improving strength and corrosion resistance.
It has achieved high strength and excellent corrosion resistance of aluminum alloy materials, with tensile strength ≥520MPa, yield strength ≥460MPa, elongation ≥10%, and peeling corrosion performance is not lower than P level. It is suitable for equipment serving in marine atmospheric environments.
Smart Images

Figure CN119876704A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloys, and in particular to a high-strength, corrosion-resistant aluminum alloy material and a preparation method and application thereof. Background Art
[0002] Aluminum alloys are widely used in structural and load-bearing parts such as ships, carrier-based aircraft, and radar equipment serving in the marine atmospheric environment due to their low density, high specific strength, and excellent forming properties. The marine atmospheric environment is complex and changeable, with significant characteristics such as high temperature, high humidity, and high salt spray. When in service, the current aluminum alloy materials will be subject to corrosion due to the multi-factor coupling of the marine atmospheric environment, which may cause structural damage or loss of function of structural parts or load-bearing parts, which is extremely harmful. For safe service in marine operations, the corrosion resistance of aluminum alloy materials seriously affects the safety and service life of ships, carrier-based aircraft, and radar equipment. The development of aluminum alloy materials with both high strength and excellent corrosion resistance is a key issue in the research and widespread application of aluminum alloys serving in the marine atmospheric environment.
[0003] The aluminum alloy materials used in the structural parts and load-bearing parts of the current marine equipment are mainly heat-treatable and strengthened aluminum alloys such as 2xxx series, 6xxx series and 7xxx series. 2xxx series Al-Cu alloys and 7xxx series Al-Zn-Mg-Cu alloys have been widely used due to their good strength and toughness. However, the corrosion resistance of these alloys cannot meet the service requirements of the marine atmospheric environment, especially when used under peak aging conditions. The exfoliation corrosion and intergranular corrosion behavior of Al-Cu alloys and Al-Zn-Mg-Cu alloys are attributed to the copper-poor non-precipitation zone caused by the precipitation of Al2Cu phase and MgZn2 phase at the grain boundary. The potential of the non-precipitation zone is lower than that of the matrix, forming a galvanic cell for anodic dissolution, resulting in intergranular corrosion and exfoliation corrosion. The strength loss and delayed fracture sensitivity caused by hydrogen-induced cracking under stress are also the main problems of Al-Zn-Mg-Cu alloy plates. 5xxx series Al-Mg alloys are widely used in ships and armored vehicles due to their excellent corrosion resistance, weldability and formability, but the strength of Al-Mg alloy plates cannot meet the safety standards of key load-bearing structural parts. It is difficult for existing aluminum alloy materials to balance strength and corrosion performance when serving in the marine atmosphere. It is necessary to develop new aluminum alloy materials with better environmental adaptability to meet the increasingly stringent service requirements of ships, carrier-based aircraft, radars and other equipment.
[0004] Compared with 2xxx and 7xxx age-hardened alloys, the strength of 5xxx alloys is significantly lower. Adding Zn to Al-Mg alloys can precipitate T-Mg 32 (Al, Zn) 49Phase or η-MgZn2 phase can significantly improve the precipitation kinetics and aging hardening response. Related studies have shown that adding 2.8wt% Zn to Al-6Mg alloy increases the strength of the alloy by 130MPa. Adding Zn to Al-Mg alloy can form T-Mg 32 (Al, Zn) 49 phase, thereby inhibiting the formation of β-Al3Mg2 phase, which helps to improve the corrosion resistance of the alloy; at the same time, the addition of Zn can effectively inhibit the segregation and diffusion of hydrogen, thereby forming hydrogen-induced cracks and inhibiting the occurrence of hydrogen-induced cracking. In addition, the addition of trace rare earth elements will significantly affect the microstructure and comprehensive properties of aluminum alloy materials. Rare earth microalloying has gradually become an important way and means to tap the potential of aluminum alloys, improve alloy properties, and develop new aluminum alloys. At present, most of the research on improving the performance of Al-Mg alloys through element design only focuses on improving the performance of one aspect of aluminum alloys, and does not fully balance the strength and corrosion resistance of aluminum alloys, and cannot meet the needs of service in marine atmospheric environments. Summary of the invention
[0005] In view of the problem that the strength and corrosion resistance of aluminum alloys in the above-mentioned prior art are difficult to meet the service requirements of marine atmosphere, the present invention provides a high-strength and corrosion-resistant aluminum alloy material and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A high-strength corrosion-resistant aluminum alloy material, the chemical composition of the aluminum alloy includes, by weight percentage: Mg 4.5-8.5%, Zn 3.5-5.5%, Cu 0.8-1.6%, at least two of the following elements with a total content not exceeding 0.5%: Mn 0.05-0.15%, Cr 0.05-0.15%, Ti 0.05-0.12%, Sc 0.06-0.16%, Er 0.08-0.14%, Zr 0.06-0.12%, and impurities with a total content not exceeding 0.4%, and the rest is Al; wherein the mass ratio of Mg / Zn is 1.1-2.0, when Sc and Zr exist at the same time, 0.15%≤(Sc+Zr)≤0.2%, when Er and Zr exist at the same time, 0.16%≤(Er+Zr)≤0.24%, and each impurity element is ≤0.15%.
[0008] Furthermore, the chemical composition of the aluminum alloy includes, by weight percentage, Mg 4.7-8.4%, Zn 3.6-5.3%, Cu 0.9-1.5%, at least two of the elements Mn, Cr, Ti, Sc, Er, and Zr with a total content not exceeding 0.45%, and the total amount of impurity elements not exceeding 0.35%, with each impurity element ≤0.13%.
[0009] Furthermore, the chemical composition of the aluminum alloy includes, by weight percentage: Mg 5-8.2%, Zn 3.8-5.2%, Cu1-1.4%, at least two of the elements Mn, Cr, Ti, Sc, Er, and Zr with a total content not exceeding 0.4%, and the total amount of impurity elements not exceeding 0.3%, with each impurity element ≤0.12%.
[0010] Furthermore, when Mg / Zn=, 1.2%≤Cu≤1.5%; when 1.5<Mg / Zn≤2, 0.9%≤Cu<1.2%.
[0011] Furthermore, the aluminum alloy material has a tensile strength of ≥520MPa, a yield strength of ≥460MPa, and an elongation of ≥10%; the exfoliation corrosion performance is not lower than Grade P; the slow strain rate tensile test is carried out in accordance with GB / T 22640-2023, and the elongation of the aluminum alloy material in salt water is attenuated by no more than 9% compared with the inert medium; the neutral salt spray corrosion test is carried out in accordance with GB / T 10125-2021, the cycle is 960h, and the average corrosion rate is no more than 0.1g / (m 2 h).
[0012] The present invention also includes the following technical solutions:
[0013] A method for preparing a high-strength and corrosion-resistant aluminum alloy material comprises the following steps:
[0014] (1) The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots;
[0015] (2) the aluminum alloy ingot is kept at 340-420° C. for 10-24 hours for a first homogenization treatment, and then kept at 465-488° C. for 18-32 hours for a second homogenization treatment;
[0016] (3) keeping the aluminum alloy ingot after homogenization treatment at 420-470° C. for at least 5 hours, and processing the aluminum alloy ingot after homogenization treatment by one or more hot deformation methods selected from rolling, forging and extrusion to obtain an aluminum alloy processed material;
[0017] (4) subjecting the aluminum alloy processed material to a solid solution treatment at 467-485° C. for 1-4 hours;
[0018] (5) cold deformation treatment of the aluminum alloy processed material after solid solution treatment;
[0019] (6) subjecting the aluminum alloy processed material after cold deformation to single-stage or double-stage aging treatment to obtain a high-strength and corrosion-resistant aluminum alloy material; the temperature of the single-stage aging treatment is 100-132° C., and the insulation time is 18-36 h; the first-stage aging treatment temperature of the double-stage aging treatment is 75-90° C., and the insulation time is 10-16 h, and the second-stage aging treatment temperature is 105-130° C., and the insulation time is 12-24 h.
[0020] Furthermore, the aluminum alloy processed material is a plate, a forging or an extruded material.
[0021] The present invention also includes the following technical solutions:
[0022] The invention discloses an application of a high-strength and corrosion-resistant aluminum alloy material in equipment serving in marine and atmospheric environments.
[0023] The mechanism involved in the present invention is as follows:
[0024] By precisely controlling the content and mass ratio of the alloying elements Mg, Zn, and Cu in the aluminum alloy material, and by aging strengthening, T-Mg 32 (Al, Zn) 49 The dispersion precipitation of β-Al3Mg2 phase and its metastable phase makes the aluminum alloy material obtain sufficient strength; by strictly controlling the mass ratio of Mg / Zn, the element segregation near the grain boundary caused by excess Mg or Zn elements is avoided, the precipitation of β-Al3Mg2 phase at the grain boundary is suppressed, and the T-Mg 32 (Al, Zn) 49 phase discontinuous distribution; by controlling the content of Cu element, the precipitation strengthening effect is enhanced while reducing the potential difference between the matrix and the precipitated phase, thereby obtaining excellent corrosion resistance; by adding microalloying elements, a dispersed Al3M phase is formed after homogenization treatment, which plays a role in pinning grain boundaries and inhibiting recrystallization during subsequent hot working, so that the final material forms microstructure characteristics that are beneficial to improving strength and corrosion resistance, including a large range of fibrous grains and a higher degree of subgrain structure density.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention provides a high-strength corrosion-resistant aluminum alloy material and a preparation method and application thereof. By precisely controlling the content and mass ratio of Mg, Zn, and Cu elements, and reasonably adding trace elements such as Mn, Cr, Ti, Sc, Er, and Zr, the tensile strength and yield strength of the aluminum alloy are improved to reach ≥520MPa and ≥460MPa, respectively, while ensuring good elongation, and the elongation of the aluminum alloy is ≥10%. In addition, the electrochemical corrosion tendency of the precipitation phase is reduced by the balanced precipitation of alloy elements and the comprehensive regulation of the grain boundary precipitation phase, the number of corrosion initiation is reduced, and the high-density subgrain structure is combined to inhibit the channel for crack propagation, greatly improving the exfoliation corrosion, stress corrosion, and salt spray corrosion performance of the alloy, so that the exfoliation corrosion performance of the aluminum alloy material is not lower than P grade; in a slow strain rate tensile test in salt water, the elongation is attenuated by no more than 9% compared with the inert medium, showing good resistance to stress corrosion cracking; in a 960h neutral salt spray corrosion test, the average corrosion rate is no more than 0.1g / (m 2 h), which makes the aluminum alloy material have irreplaceable advantages in situations where it needs to withstand high stress and high corrosion environments, and meets the application requirements of structural parts or load-bearing parts of equipment serving in marine atmospheric environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0028] Figure 1 The figure shows the comparison of tensile strength and exfoliation corrosion performance of the embodiments of the present invention and the comparative examples;
[0029] Figure 2 The comparison of tensile strength and stress corrosion performance of the embodiments of the present invention and the comparative examples is shown;
[0030] Figure 3 The comparison of tensile strength and neutral salt spray corrosion performance of the embodiments of the present invention and the comparative examples is shown;
[0031] Figure 4 The EBSD structure of the grains of the aluminum alloy in Example 1 is shown;
[0032] Figure 5 TEM images of the precipitation phases within the aluminum alloy crystals and at the grain boundaries in Example 3 are shown. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Example 1
[0035] The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; the obtained aluminum alloy ingots are kept at 380°C for 12 hours for a first-level homogenization treatment, and then kept at 475°C for 24 hours for a second-level homogenization treatment; the aluminum alloy ingots after homogenization treatment are kept at 420°C for 10 hours and then hot rolled with a total deformation of 60% to obtain aluminum alloy plates; the obtained aluminum alloy plates are kept at 475°C for 2 hours for solution treatment; the aluminum alloy plates after solution treatment are cold deformed to reduce residual stress; the aluminum alloy plates after cold deformation treatment are subjected to single-stage aging treatment, the temperature of the single-stage aging treatment is 125°C, and the insulation time is 32 hours to obtain high-strength and corrosion-resistant aluminum alloy materials.
[0036] The components and weight percentages of the high-strength and corrosion-resistant aluminum alloy material in this embodiment are: Mg 4.7%, Zn 3.6%, Cu 1.2%, Mn 0.12%, Cr 0.11%, Sc 0.12%, Zr 0.08%, Fe 0.08%, Si 0.06%, and the rest is Al.
[0037] Example 2
[0038] The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; the obtained aluminum alloy ingots are kept at 360°C for 20 hours for a first-stage homogenization treatment, and then kept at 467°C for 32 hours for a second-stage homogenization treatment; the aluminum alloy ingots after homogenization treatment are kept at 440°C for 8 hours and then free forged to obtain aluminum alloy forgings; the obtained aluminum alloy forgings are kept at 485°C for 1.5 hours for solid solution treatment; the aluminum alloy forgings after solid solution treatment are cold deformed to reduce residual stress; the aluminum alloy forgings after cold deformation treatment are subjected to single-stage aging treatment, the temperature of the single-stage aging treatment is 115°C, and the holding time is 36 hours to obtain high-strength and corrosion-resistant aluminum alloy materials.
[0039] The components and weight percentages of the high-strength and corrosion-resistant aluminum alloy material in this embodiment are: Mg 5.0%, Zn 3.8%, Cu 1.5%, Cr 0.09%, Ti 0.09%, Er 0.11%, Zr 0.1%, Fe 0.08%, Si 0.06%, and the rest is Al.
[0040] Example 3
[0041] The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; the obtained aluminum alloy ingots are kept at 410°C for 10 hours for a first-level homogenization treatment, and then kept at 485°C for 20 hours for a second-level homogenization treatment; the aluminum alloy ingots after homogenization treatment are kept at 460°C for 6 hours and then rolled to obtain aluminum alloy rolled plates; the obtained aluminum alloy rolled plates are kept at 480°C for 2 hours for a solid solution treatment; the aluminum alloy rolled plates after the solid solution treatment are cold deformed to reduce residual stress; the aluminum alloy rolled plates after the cold deformation treatment are subjected to a double-stage aging treatment, the first-level aging treatment temperature is 75°C, the insulation time is 16 hours, and the second-level aging treatment temperature is 130°C, the insulation time is 12 hours, to obtain high-strength and corrosion-resistant aluminum alloy materials.
[0042] The components and weight percentages of the high-strength and corrosion-resistant aluminum alloy material in this embodiment are: Mg 6.2%, Zn 4.0%, Cu 1.1%, Mn 0.08%, Sc 0.08%, Er 0.09%, Zr 0.09%, Fe 0.07%, Si 0.08%, and the rest is Al.
[0043] Example 4
[0044] The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; the obtained aluminum alloy ingots are kept at 360°C for 15 hours for a first-level homogenization treatment, and then kept at 467°C for 32 hours for a second-level homogenization treatment; the aluminum alloy ingots after homogenization treatment are kept at 470°C for 5 hours and then extruded to obtain aluminum alloy extrusions; the obtained aluminum alloy extrusions are kept at 470°C for 4 hours for solution treatment; the aluminum alloy extrusions after the solution treatment are cold deformed to reduce residual stress; the aluminum alloy rolled plate after the cold deformation treatment is subjected to a double-stage aging treatment, the first-level aging treatment temperature is 85°C, the insulation time is 10 hours, and the second-level aging treatment temperature is 110°C, the insulation time is 18 hours, to obtain high-strength and corrosion-resistant aluminum alloy materials.
[0045] The components and weight percentages of the high-strength and corrosion-resistant aluminum alloy material in this embodiment are: Mg 7.2%, Zn 3.8%, Cu 1.0%, Mn 0.10%, Cr 0.07%, Zr 0.11%, Fe 0.08%, Si 0.08%, and the rest is Al.
[0046] Example 5
[0047] The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; the obtained aluminum alloy ingots are kept at 340°C for 24 hours for a first-level homogenization treatment, and then kept at 488°C for 32 hours for a second-level homogenization treatment; the aluminum alloy ingots after homogenization treatment are kept at 420°C for 10 hours and then rolled to obtain aluminum alloy rolled plates; the obtained aluminum alloy rolled plates are kept at 480°C for 2 hours for a solid solution treatment; the aluminum alloy extrusions after the solid solution treatment are cold deformed to reduce residual stress; the aluminum alloy rolled plates after the cold deformation treatment are subjected to a double-stage aging treatment, the first-stage aging treatment temperature is 90°C, the insulation time is 10 hours, and the second-stage aging treatment temperature is 105°C, the insulation time is 24 hours, to obtain high-strength and corrosion-resistant aluminum alloy materials.
[0048] The components and weight percentages of the high-strength and corrosion-resistant aluminum alloy material in this embodiment are: Mg 8.4%, Zn 5.2%, Cu 1.0%, Cr 0.10%, Ti 0.08%, Fe 0.08%, Si 0.07%, and the rest is Al.
[0049] Example 6
[0050] The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; the obtained aluminum alloy ingots are kept at 420°C for 10 hours for a first-level homogenization treatment, and then kept at 465°C for 18 hours for a second-level homogenization treatment; the aluminum alloy ingots after homogenization treatment are kept at 465°C for 5 hours and then rolled to obtain aluminum alloy rolled plates; the obtained aluminum alloy rolled plates are kept at 475°C for 2 hours for a solid solution treatment; the aluminum alloy extrusions after the solid solution treatment are cold deformed to reduce residual stress; the aluminum alloy rolled plates after the cold deformation treatment are subjected to a double-stage aging treatment, the first-level aging treatment temperature is 90°C, the insulation time is 10 hours, and the second-level aging treatment temperature is 105°C, the insulation time is 24 hours, to obtain high-strength and corrosion-resistant aluminum alloy materials.
[0051] The components and weight percentages of the high-strength and corrosion-resistant aluminum alloy material in this embodiment are: Mg 8.0%, Zn 4.0%, Cu 0.9%, Sc 0.09%, Er 0.14%, Zr 0.08%, Fe 0.09%, Si 0.08%, and the rest is Al.
[0052] Comparative Example 1
[0053] The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; the obtained aluminum alloy ingots are kept at 485°C for 12 hours for single-stage homogenization treatment; the aluminum alloy ingots after homogenization treatment are kept at 460°C for 6 hours and then rolled to obtain aluminum alloy rolled plates; the obtained aluminum alloy rolled plates are kept at 480°C for 2 hours for solid solution treatment; the aluminum alloy extrusions after solid solution treatment are cold deformed to reduce residual stress; the aluminum alloy rolled plates after cold deformation treatment are subjected to single-stage aging treatment, the temperature of the single-stage aging treatment is 120°C, and the insulation time is 24 hours to obtain aluminum alloy materials.
[0054] The components and weight percentages of the aluminum alloy material in this comparative example are: Mg 6.2%, Zn 1.5%, Cu 2%, Cr 0.08%, Ti 0.06%, Er 0.07%, Zr 0.08%, Fe 0.06%, Si 0.06%, and the rest is Al.
[0055] Comparative Example 2
[0056] The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; the obtained aluminum alloy ingots are kept at 360°C for 20 hours for a first-level homogenization treatment, and then kept at 467°C for 32 hours for a second-level homogenization treatment; the aluminum alloy ingots after homogenization treatment are kept at 400°C for 10 hours and then rolled to obtain aluminum alloy rolled plates; the obtained aluminum alloy rolled plates are kept at 480°C for 2 hours for a solid solution treatment; the aluminum alloy extruded materials after the solid solution treatment are cold deformed to reduce residual stress; the aluminum alloy rolled plates after the cold deformation treatment are subjected to a double-stage aging treatment, the first-stage aging treatment temperature is 90°C, the insulation time is 10 hours, and the second-stage aging treatment temperature is 105°C, the insulation time is 24 hours, to obtain aluminum alloy materials.
[0057] The components and weight percentages of the aluminum alloy material in this comparative example are: Mg 4.0%, Zn 4.2%, Cu 0.6%, Cr 0.06%, Sc 0.12%, Zr 0.09%, Fe 0.11%, Si 0.07%, and the rest is Al.
[0058] Comparative Example 3
[0059] The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; the obtained aluminum alloy ingots are kept at 360°C for 20 hours for a first-level homogenization treatment, and then kept at 467°C for 32 hours for a second-level homogenization treatment; the aluminum alloy ingots after homogenization treatment are kept at 460°C for 6 hours and then rolled to obtain aluminum alloy rolled plates; the obtained aluminum alloy rolled plates are kept at 480°C for 2 hours for a solid solution treatment; the aluminum alloy extruded materials after the solid solution treatment are cold deformed to reduce residual stress; the aluminum alloy rolled plates after the cold deformation treatment are subjected to a double-stage aging treatment, the first-stage aging treatment temperature is 100°C, the insulation time is 8 hours, and the second-stage aging treatment temperature is 135°C, the insulation time is 15 hours, to obtain aluminum alloy materials.
[0060] The components and weight percentages of the aluminum alloy material in this comparative example are: Mg 6.0%, Zn 3.2%, Cu 0.2%, Mn 0.03%, Cr 0.02%, Fe 0.09%, Si 0.07%, and the rest is Al.
[0061] Attached Figure 1-3 Table 1 shows the tensile strength, yield strength, elongation, exfoliation corrosion, stress corrosion and neutral salt spray corrosion properties of the aluminum alloy plates, forgings or extrusions prepared in the embodiments of the present invention and the comparative examples. Figure 1-3 As can be seen from Table 1, the comprehensive performance of the aluminum alloy material in the embodiment is significantly better than that in the comparative example.
[0062] Table 1 Performance of aluminum alloy materials in Examples and Comparative Examples
[0063]
[0064] Attached Figure 4 EBSD organization diagram of the grains of the aluminum alloy plate in Example 1; Figure 5 TEM images of the intragranular and grain boundary precipitation phases of the aluminum alloy plate in Example 3. It can be seen that the present invention controls the type and content of microalloying elements, forms a dispersed Al3M phase after homogenization treatment, and matches a suitable hot deformation process to minimize the proportion of recrystallization in the material, so that the final plate obtains a higher subgrain density, forming a microstructure feature that is beneficial to improving strength and corrosion resistance.
[0065] The present invention provides a high-strength corrosion-resistant aluminum alloy material and a preparation method and application thereof. By precisely controlling the content and mass ratio of Mg, Zn, and Cu elements, and reasonably adding trace elements such as Mn, Cr, Ti, Sc, Er, and Zr, the tensile strength and yield strength of the aluminum alloy are improved to reach ≥520MPa and ≥460MPa, respectively, while ensuring good elongation, and the elongation of the aluminum alloy is ≥10%. In addition, the electrochemical corrosion tendency of the precipitation phase is reduced by the balanced precipitation of alloy elements and the comprehensive regulation of the grain boundary precipitation phase, the number of corrosion initiation is reduced, and the high-density subgrain structure is combined to inhibit the channel for crack propagation, greatly improving the exfoliation corrosion, stress corrosion, and salt spray corrosion performance of the alloy, so that the exfoliation corrosion performance of the aluminum alloy material is not lower than P grade; in a slow strain rate tensile test in salt water, the elongation is attenuated by no more than 9% compared with the inert medium, showing good resistance to stress corrosion cracking; in a 960h neutral salt spray corrosion test, the average corrosion rate is no more than 0.1g / (m 2 h), which makes the aluminum alloy material have irreplaceable advantages in situations where it needs to withstand high stress and high corrosion environments, and meets the application requirements of structural parts or load-bearing parts of equipment serving in marine atmospheric environments.
[0066] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. A high-strength, corrosion-resistant aluminum alloy material, characterized in that: The chemical composition of the aluminum alloy includes, by weight percentage, Mg 4.5-8.5%, Zn 3.5-5.5%, Cu 0.8-1.6%, at least two of the following elements with a total content not exceeding 0.5%: Mn 0.05-0.15%, Cr 0.05-0.15%, Ti 0.05-0.12%, Sc 0.06-0.16%, Er 0.08-0.14%, Zr0.06-0.12%, and impurities with a total content not exceeding 0.4%, and the rest is Al; wherein, the mass ratio of Mg / Zn=1.1-2.0, when Sc and Zr exist at the same time, 0.15%≤(Sc+Zr)≤0.2%, when Er and Zr exist at the same time, 0.16%≤(Er+Zr)≤0.24%, and each impurity element is ≤0.15%.
2. The high-strength and corrosion-resistant aluminum alloy material according to claim 1, characterized in that: The chemical composition of the aluminum alloy includes, by weight percentage: Mg 4.7-8.4%, Zn 3.6-5.3%, Cu 0.9-1.5%, at least two of the elements Mn, Cr, Ti, Sc, Er, and Zr with a total content not exceeding 0.45%, the total amount of impurity elements not exceeding 0.35%, and each impurity element ≤ 0.13%.
3. The high-strength and corrosion-resistant aluminum alloy material according to claim 2, characterized in that: The chemical composition of the aluminum alloy includes by weight percentage: Mg 5-8.2%, Zn 3.8-5.2%, Cu 1-1.4%, at least two of the elements Mn, Cr, Ti, Sc, Er, and Zr with a total content not exceeding 0.4%, and the total amount of impurity elements does not exceed 0.3%, and each impurity element is ≤0.12%.
4. The high-strength and corrosion-resistant aluminum alloy material according to claim 1, characterized in that: When 1.1≤Mg / Zn≤1.5, 1.2%≤Cu≤1.5%; when 1.5<Mg / Zn≤2, 0.9%≤Cu<1.2%.
5. A high-strength, corrosion-resistant aluminum alloy material according to any one of claims 1 to 3, characterized in that: The aluminum alloy material has a tensile strength of ≥520MPa, a yield strength of ≥460MPa, and an elongation of ≥10%; the exfoliation corrosion performance is not lower than P grade; the slow strain rate tensile test is carried out in accordance with GB / T 22640-2023, and the elongation of the aluminum alloy material in salt water is attenuated by no more than 9% compared with the inert medium; the neutral salt spray corrosion test is carried out in accordance with GB / T 10125-2021, the cycle is 960h, and the average corrosion rate is no more than 0.1g / (m 2 h).
6. A method for preparing the high-strength and corrosion-resistant aluminum alloy material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) The raw materials of high-strength and corrosion-resistant aluminum alloy materials are melted, degassed, removed from inclusions and semi-continuously cast to obtain aluminum alloy ingots; (2) the aluminum alloy ingot is kept at 340-420° C. for 10-24 hours for a first homogenization treatment, and then kept at 465-488° C. for 18-32 hours for a second homogenization treatment; (3) keeping the aluminum alloy ingot after homogenization treatment at 420-470° C. for at least 5 hours, and processing the aluminum alloy ingot after homogenization treatment by one or more hot deformation methods selected from rolling, forging and extrusion to obtain an aluminum alloy processed material; (4) subjecting the aluminum alloy processed material to a solid solution treatment at 467-485° C. for 1-4 hours; (5) cold deformation treatment of the aluminum alloy processed material after solid solution treatment; (6) subjecting the aluminum alloy processed material after cold deformation to single-stage or double-stage aging treatment to obtain a high-strength and corrosion-resistant aluminum alloy material; the temperature of the single-stage aging treatment is 100-132° C., and the insulation time is 18-36 h; the first-stage aging treatment temperature of the double-stage aging treatment is 75-90° C., and the insulation time is 10-16 h, and the second-stage aging treatment temperature is 105-130° C., and the insulation time is 12-24 h.
7. The method for preparing a high-strength and corrosion-resistant aluminum alloy material according to claim 6, characterized in that: The aluminum alloy processed material is a plate, a forging or an extruded material.
8. Use of the high-strength, corrosion-resistant aluminum alloy material according to any one of claims 1 to 3 in equipment serving in marine and atmospheric environments.
Citation Information
Cited By
Lightweight high-strength high-toughness high-magnesium-content Al-Mg-Zn aluminum alloy and preparation method thereof
CN121718770A
A lightweight high-strength high-toughness high-magnesium-content Al-Mg-Zn aluminum alloy and a preparation method thereof
CN121718770B
Ultrahigh-strength, high-toughness and high-magnesium-content Al-Mg-Zn aluminum alloy and preparation method thereof
CN121718773A
An ultrahigh-strength high-toughness high-magnesium-content Al-Mg-Zn aluminum alloy and a preparation method thereof
CN121718773B
7-series aluminum alloy and preparation method and application thereof
CN121802249A